The circulation and legal transplant of the Spanish model of arbitration constituted by will in Latin America: between improvements and future prospects - Ferrante, Alfredo (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The article studies the evolution of the Spanish model of arbitration constituted by will, a model that has been used as inspiration in Latin America, in countries such as Bolivia, Peru and Honduras. Through a methodology in legal comparison, it will be observed how the initial Spanish model remains tendentially static, while Latin American legislators, adopting a more dynamic behavior, led to the creation of several models that improve the regulation from which inspiration has been taken.
Keywords: Arbitration constituted by will; Comparative law; legal transplant; rt. 10 Spanish arbitration act; Latin America